A Collaboration Among Primary Care–Based Clinical Pharmacists and Community‐Based Health Coaches. Issue 1 (7th October 2020) - Sorensen, Andrea; Grotts, Jonathan F.; Tseng, Chi‐Hong; Moreno, Gerardo; Maranon, Richard; Whitmire, Natalie; Viramontes, Omar; Atkins, Sandy; Sefilyan, Ester; Simmons, June W.; Mangione, Carol M.
Abstract : BACKGROUND/OBJECTIVES: Medication discrepancies and adverse drug events are common following hospital discharge. This study evaluates whether a collaboration between community‐based health coaches and primary care–based pharmacists was associated with a reduction in inpatient utilization following hospitalization. DESIGN: Retrospective cohort study using propensity score matching. SETTING: Urban academic medical center and surrounding community. PARTICIPANTS: Intervention patients (n = 494) were adults aged 65 and older admitted to the University of California, Los Angeles (UCLA) Ronald Reagan Medical Center during the study period and who met study inclusion criteria. A matched‐control group was composed of patients with similar demographic and clinical characteristics who were admitted to the study site during the study period but who received usual care (n = 2, 470). A greedy algorithm approach was used to conduct the propensity score match. INTERVENTION: Following acute hospitalization, a health coach conducted a home visit and transmitted all medication‐related information to a pharmacist based in a primary care practice. The pharmacist compared this information with the patient's electronic medical record medication list and consulted with the patient's primary care provider to optimize medication management. MEASUREMENTS: Thirty‐day readmissions (primary outcome), 60‐ and 90‐day readmissions, and 30‐day emergency department (ED) visits (secondary outcomes) to UCLA Health. RESULTS: Among 494 patients who received the intervention, 307 (62.1%) were female with a mean age of 83.0 years (interquartile range [IQR] = 76–90 years). Among 2, 470 matched‐control patients, 1, 541 (62.4%) were female with a mean age of 82.7 years (IQR = 74.9–89.5 years). For the propensity score match, standardized mean differences were below .1 for 23 of 25 variables, indicating good balance. Patients who received this intervention had a significantly lower predicted probability of being readmitted within 30 days compared with matched‐control patients (10.6%; 95% confidence interval [CI] = 7.9–13.2) vs 21.4%; 95% CI = 19.8–23.0; P value < .001). CONCLUSION: A home visit conducted by a health coach combined with a medication review by a primary care–based pharmacist may prevent subsequent inpatient utilization.